Stability studies of cuticle degrading and mycolytic enzymes of myrothecium verrucaria for control of insect pests and fungal phytopathogens - Chavan, S. B; Vidhate, R. P.; Kallure, G. S.; Dandawate, N. L.; Khire, J. M.; Deshpande, M. V. (Indian Journal of Biotechnology, 2017)
Myrothecium verrucaria produced extracellularly hydrolytic enzymes which can hydrolyse the insect cuticle as well as fungal cell wall. The addition of polyols, such as glycerol, sorbitol, xylitol (1 M) during ultra -filtration or freeze- drying of enzyme mixture increased the recovery of the enzymes in a concentrated form. Polyols (5 M) increased the temperature and pH stability of the enzymes, in the presence of glycerol chitinase, beta-1,3-glucanase, lipase and protease retained 50-60% of initial activities at 40 degrees C after 3 h. While xylitol (5 M) was effective in stabilizing activities at pH 5.0 and 7.5 at 25 degrees C for 7 d. In the freeze-dried powder form, > 90% at 4 degrees C for 1 year and 80-85% at 25 degrees C for 2 months enzyme activities were retained. The addition of glycerol (1 M) to the enzyme mixture protected enzyme activities under sunlight (60-65% activity at RT) for 5 d. Because of glycerol (1 M), the efficacy of M verrucaria enzyme preparation to control Helicoverpa armigera infestation in chick pea was increased to 70 +/- 19%. While without glycerol the efficacy was 55 +/- 23%. The germination of peanut seeds infected with Sclerotium rolfsii was observed to be increased (70 +/- 5%) in a pot irrigated with enzyme mixture.

Characterization of novel acidic and thermostable phytase secreting Streptomyces sp. (NCIM 5533) for plant growth promoting characteristics - Puppala, K. R.; Bhavsar, K.; Sonalkar, V.; Khire, J. M.; Dharne, M. S. (Biocatalysis and Agricultural Biotechnology, 2019)
Successful agricultural practices in acidic and arid region soils are still challenging worldwide. We investigated Actinomycete strain obtained from soil, which was found to produce extracellular phytase having the optimum pH, temperature of 2.5 and 70 °C, respectively and Plant growth promoting (PGP) attributes. These abilities of the phytase make it novel as compared to other Streptomyces derived phytases. Strain was also evaluated for physiological traits such as salinity, temperature, and pH followed by morphological and molecular identification. The Streptomyces sp. strain (NCIM 5533) displayed additional PGP traits such as indole-3-acetic acid (IAA), ammonia and phosphate solubilization activity. A significant increment in Tomato plant (Solanum lycopersicum) root, shoot and as well as total height in bioassays at laboratory scale and green house level and its ability to colonize roots substantiated its potency as a true plant growth promoting rhizobacteria (PGPR). To our knowledge this is the first report of Streptomyces sp. having the ability to produce acidic and thermostable phytase as well as PGP traits showing enhanced plant growth could have implications in soils having acidic nature and also in arid region.